2010
DOI: 10.1364/boe.1.000943
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical signals in response to peripheral nerve stimulation reflect skeletal muscle kinematics

Abstract: Previously we have reported a near-infrared optical response in the region occupied by a peripheral nerve that is distal to the site of electrical stimulation of that peripheral nerve. This “intermediate” signal is vascular in nature but its biological origin not been elucidated. In the present study, an animal model of the signal has been created and our human studies expanded to directly investigate the contribution of non-artifactual vascular motion induced by muscle contraction to the biological origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The detailed study by Erb et al . 9 concluded that the optical signals in the later regime are related to the motion of blood vessels in the measurement volume during stimulus-induced muscle contraction. All together, while the present study concludes that optical signals in the early regime are related to the excitation–contraction process, the previous studies conclude that optical signals in the later regime are related to the mechanical motion.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed study by Erb et al . 9 concluded that the optical signals in the later regime are related to the motion of blood vessels in the measurement volume during stimulus-induced muscle contraction. All together, while the present study concludes that optical signals in the early regime are related to the excitation–contraction process, the previous studies conclude that optical signals in the later regime are related to the mechanical motion.…”
Section: Discussionmentioning
confidence: 99%
“…The results are summarized in table 1 and detailed in sections 3.2 – 3.7 and elsewhere 5, 6 . In the animal model, optical signals were completely eliminated following both pharmacological and surgical separation of the nerve from the muscles it innervates.…”
Section: Resultsmentioning
confidence: 99%
“…The timescale of the signals and their wavelength dependence suggested that changes in absorption, rather than scattering, associated with tissue hemodynamic events were likely to underlie those changes. In the present work, we report further studies on the spatial and spectral dependence of these signals, as well as the contribution of stimulus-induced motion and the effect of vascular occlusion, the results of which have been recently published 5, 6 . We also discuss ongoing work aimed at understanding the usefulness of these signals for non-invasively assessing the health of both nerve and muscle.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Chen et al [ 19 ] report on a study of the spatial and spectral dependence of the optical signals induced by stimulation of the human median and sural nerves. In a companion paper by the same group of researchers, Erb et al [ 20 ] focuses on the contribution of non-artifactual vascular motion induced by muscle contraction to the biological origin of the same signal. The influence of muscle fiber motion during exercise on diffuse correlation spectroscopy (DCS) measurements of skeletal muscle blood flow is explored by Shang et al [ 21 ].…”
mentioning
confidence: 99%